International experience of crime investigation in the field of human trafficking - Buhaiov, Yaroslav Y.; Koretskyi, Oleh P.; Koretska, Viktoriia V.; Penkov, Serhii V.; Shapar, Artem O. (Amazonia Investiga, 2021)
The paper aims to define an effective anti-human trafficking system in Ukraine. On the basis of theoretical information and international experience systematic analysis, the peculiarities of investigating crimes in the field of human trafficking are identified: timely receipt of information concerning crimes commission, assigning a case of human trafficking to an investigator or prosecutor with positive experience in detecting such crimes, cooperation of law enforcement agencies with each other and law enforcement agencies of other states in regard to effective ways of such crimes investigation, an effective system of human trafficking victims support. It is possible to increase the effectiveness of combating human trafficking through activities in the following areas: training of law enforcement officers in accordance with international standards; exchange of experience between Ukrainian law enforcement officers with the employees of relevant institutions of other countries; enshrinement at the statutory level of stricter responsibility for such crimes commission; monitoring the compliance of the Ukrainian anti-human trafficking system activities with international standards; creation of a comprehensive support system for human trafficking victims.